2015
DOI: 10.1007/s10072-015-2099-z
|View full text |Cite
|
Sign up to set email alerts
|

Using event-related potential P300 as an electrophysiological marker for differential diagnosis and to predict the progression of mild cognitive impairment: a meta-analysis

Abstract: P300 event-related potential component may sensitively predict mild cognitive impairment (MCI) progression. Here, pooled effect size estimates of P300 amplitude and latency were computed at midline electrodes among controls, MCI patients, and Alzheimer's disease (AD) patients. Baseline data were compared to one-year follow-up data. MCI patients showed decreased P300 amplitude and prolonged latency compared to controls. Pooled standardized mean differences (SMDs) were -0.67 (95 % CI -1.12 to -0.23, P = 0.003) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 40 publications
0
54
0
2
Order By: Relevance
“…The elderly with aMCI showed longer P3 latencies in homogenous and heterogeneous conditions in the current study compared to the controls, suggesting decreased efficacy of perceptual/central processing time with regard to performing a cognitive task requiring frequent updating and switching of task sets [53]. Previous research reported that the P3 latency was stable and sensitive in cognitive evaluations of MCI patients and those with conversion from MCI to AD [23]. Indeed, a number of experimental studies also demonstrated prolonged P3 latency in the elderly with aMCI [21,72] and MCI [73][74][75] when performing the visual and auditory oddball tasks.…”
Section: Discussionmentioning
confidence: 38%
See 3 more Smart Citations
“…The elderly with aMCI showed longer P3 latencies in homogenous and heterogeneous conditions in the current study compared to the controls, suggesting decreased efficacy of perceptual/central processing time with regard to performing a cognitive task requiring frequent updating and switching of task sets [53]. Previous research reported that the P3 latency was stable and sensitive in cognitive evaluations of MCI patients and those with conversion from MCI to AD [23]. Indeed, a number of experimental studies also demonstrated prolonged P3 latency in the elderly with aMCI [21,72] and MCI [73][74][75] when performing the visual and auditory oddball tasks.…”
Section: Discussionmentioning
confidence: 38%
“…Although MCI syndrome is defined as greater than expected cognitive declines based on education and age, and older adults with MCI compared to age-matched controls exhibit impairments in complex activities of daily living [63,64], MCI has often been shown to have no significant effects on daily activities [1,23]. Since the item scores of the SFPF test are associated with independent functioning in the elderly [60], the present study's comparable scores on the SFPF test in aMCI and control groups, except for lower body flexibility, indicate that older adults with aMCI might still have sufficient capacities to show intact overall daily functioning and maintain their usual daily activities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…P3 latency can be used as a sensitive index of early cognitive decline or mild cognitive dysfunction in patients with disease progression. 23 ERP can be used to evaluate the information transfer and cognitive function of the visual cortex in patients with migraine. Clinical studies suggest that a small N270 amplitude is associated with serious symptoms of anxiety and depression.…”
Section: Migraine and Event-related Potentialmentioning
confidence: 99%